2013
DOI: 10.1086/669519
|View full text |Cite
|
Sign up to set email alerts
|

Predicting High Prevalence of Community Methicillin-Resistant Staphylococcus aureus Strains in Nursing Homes

Abstract: We assessed characteristics associated with community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) carriage among residents of 22 nursing homes. Of MRSA-positive swabs, 25% (208/824) were positive for CA-MRSA. Median facility CA-MRSA percentage was 22% (range, 0%–44%). In multivariate models, carriage was associated with age less than 65 years (odds ratio, 1.2; P < .001) and Hispanic ethnicity (odds ratio, 1.2; P = .006). Interventions are needed to target CA-MRSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 10 publications
3
21
0
Order By: Relevance
“…14 Similar studies in other countries have reported MRSA prevalence rates in NHs ranging from 1.1% in Germany to 6.2% in Israel, 8.6% in Ireland, 19.5% in Belgium, 15 19%-22% in Leeds (UK), 16 and 24% in the US. 17 The range of MRSA carriage varies widely among institutions, but similar findings have been described in other studies. [15][16][17] In the present study, 2 NHs had 0% MRSA carriage.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…14 Similar studies in other countries have reported MRSA prevalence rates in NHs ranging from 1.1% in Germany to 6.2% in Israel, 8.6% in Ireland, 19.5% in Belgium, 15 19%-22% in Leeds (UK), 16 and 24% in the US. 17 The range of MRSA carriage varies widely among institutions, but similar findings have been described in other studies. [15][16][17] In the present study, 2 NHs had 0% MRSA carriage.…”
Section: Discussionsupporting
confidence: 82%
“…17 The range of MRSA carriage varies widely among institutions, but similar findings have been described in other studies. [15][16][17] In the present study, 2 NHs had 0% MRSA carriage. The prevalence of indwelling devices was much lower than reported in previous studies.…”
Section: Discussionsupporting
confidence: 82%
“…19 The first published report in Bangladesh about MRSA isolates was made in 1991 24 and thereafter focus on the burden of MRSA was reported in a number of scientific articles. 25,26 The majority of the studies mainly highlight Bangladeshi AR as similar to the global burden. MRSA infection was reported 37.2% and 21.6% respectively in hospitalized and non-hospitalized diabetic patients respectively in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…None of the isolates reported here were attributed to community-associated MRSA (CA-MRSA) or livestockassociated MRSA (LA-MRSA). That CA-MRSA can represent a substantial proportion of MRSA in nursing home residents has been reported from the US [49], and LA-MRSA has been identified among isolates from Dutch nursing homes [50]. In Germany, CA-MRSA is not common so far, nor is LA-MRSA as nasal coloniser and infectious agent in regions of Germany with low density of livestock farming such as the Rhine-Main region [51].…”
Section: Discussionmentioning
confidence: 99%